2014
DOI: 10.1159/000365105
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Measurements in Patients with Completely Ruptured Anterior Cruciate Ligament before and after RegentK and Physiotherapy

Abstract: Background: The goal of this study was to investigate acute effects of a special kind of manual therapy developed by Mohamed Khalifa (RegentK) compared to standard physiotherapy on regional oxygen saturation (rSO2) of knee tissues in patients with completely ruptured anterior cruciate ligament (ACL). Methods: Twenty patients were enrolled in this study and randomly assigned to receive either RegentK (group A; n = 10, 8 female, 2 male, mean age ± SD 31.3 ± 8.5 years) or physiotherapy (group B; n = 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Based on this study, we concluded that manual therapy influences the hemodynamics of muscles and deeper structures. The results also serve to quantify the effects of non-pharmacological and non-surgical interventions on the microvascular circulation in deep tissue after a complete rupture of the ACL [6]. …”
Section: Regional Oxygen Saturation Of Deeper Knee Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this study, we concluded that manual therapy influences the hemodynamics of muscles and deeper structures. The results also serve to quantify the effects of non-pharmacological and non-surgical interventions on the microvascular circulation in deep tissue after a complete rupture of the ACL [6]. …”
Section: Regional Oxygen Saturation Of Deeper Knee Tissuesmentioning
confidence: 99%
“…Note the higher temperature in the injured knee compared to the control knee before treatment, whereas the temperature of the foot on the injured leg is initially lower than the temperature of the foot on the healthy leg (compare the colour of the toes). Modified from Litscher et al [6]. …”
Section: Thermographic Measurementsmentioning
confidence: 99%
“…Apart from those mentioned by Pan and Zhou [4], new technical applications in manual therapy have to be mentioned here; further details on this topic can be found in an original paper published this year in this journal, too [5]. …”
Section: Figmentioning
confidence: 99%